Reversibility of severe mitral valve regurgitation after left ventricular assist device implantation: single-centre observations from a real-life population of patients. (16th January 2018) - Dobrovie, Monica; Spampinato, Ricardo A; Efimova, Elena; da Rocha e Silva, Jaqueline G; Fischer, Julia; Kuehl, Michael; Voigt, Jens-Uwe; Belmans, Ann; Ciarka, Agnieszka; Bonamigo Thome, Fernanda; Schloma, Valerie; Dmitrieva, Yaroslava; et al.
Abstract: OBJECTIVES: This study evaluates the impact of untreated preoperative severe mitral valve regurgitation (MR) on outcomes after left ventricular assist device (LVAD) implantation. METHODS: Of the 234 patients who received LVAD therapy in our centre during a 6-year period, we selected those who had echocardiographic images of good quality and excluded those who underwent mitral valve replacement prior to or mitral valve repair during LVAD placement. The 128 patients selected were divided into 2 groups: Group A with severe MR ( n  = 65) and Group B with none to moderate MR ( n  = 63, 28 with moderate MR). We evaluated transthoracic echocardiography preoperatively [15 (7–28) days before LVAD implantation; median (interquartile range)] and postoperatively up to the last available follow-up [501 (283–848) days after LVAD]. We collected mortality, complications and clinical status indicators of the patient cohort. RESULTS: We observed a significant decrease in the severity of MR after LVAD implantation (severe MR 51% pre- vs 6% post-LVAD implantation, P  < 0.001). There was no difference between groups in terms of right heart failure, rate of urgent heart transplantation, pump thrombosis or ventricular arrhythmias. There was no difference in 1-year survival and 3-year survival (87.7% vs 88.4% and 71.8% vs 66.6% for Groups A and B, respectively, P  = 0.97). CONCLUSIONS: Preoperative severe MR resolves in the majority of patients early on after LVAD implantation and is not associated with worse clinical outcomes or intermediate-term survival.